Pattern generation for multi-class LAD using iterative genetic algorithm with flexible chromosomes and multiple populations. Issue 2 (1st February 2015) - Kim, Hwang Ho; Choi, Jin Young
Highlights A pattern generation method for multi-class classification using LAD. Two decomposition approaches: one versus all, and one versus one. Iterative genetic algorithm with flexible chromosomes and multiple populations. Two control parameters: selecting patterns and deleting observations per iteration. The superiority of the suggested algorithm from a numerical experiment.